Patient safety in Dutch hospitals (Italian Journal of Public Health, 2005)
In various studies outside the Netherlands, it has been shown that a substantial number of patients suffer from some kind of harm during their treatment in hospital. The incidence of these so-called adverse events varies between 2.9% and 16.6%; it is estimated that between over a quarter and a half of these are considered to be avoidable.Preventable adverse events can be considered to be a starting point for interventions to increase patient safety. In response to this, a study was initiated in Dutch hospitals investigating the nature and extent of adverse events and their causes. Lessons learnt will be discussed within the European Research Network on Quality in Health Care (ENQual), where researchers and policy makers come together to exchange knowledge and experiences. Two important goals of the Dutch study are to reach a consensus on basic concepts and to improve research methodology. An unintended event resulting in harm caused by healthcare is called an adverse event in international literature. Preventable adverse events are especially important for prevention, in these cases the harm can be attributed to unintended events in the care process, caused by insufficient action according to professional standards and failures within the care system. Most adverse events, caused as they may seem by human action or failing to act at first sight, are often partly caused by a care process that has not been properly organized. Uniform concepts are needed in order to facilitate European comparisons, which would allow, for example, the comparison of Dutch research results with those from other countries, and the identification of specific concepts. One of the six action areas of the WHO’s World Alliance for Patient Safety is the development of a ‘patient safety taxonomy’.
Keywords: Patient safety; research; adverse events; hospitals